Community conservation and remote sensing of the desert-adapted lions in northwest Namibia - Heydinger, John (Frontiers in Ecology and Evolution, 2023)
Community-based conservation of the desert-adapted lions takes place within the semi-arid and arid environments of northwest Namibia. This area is primarily designated as communal conservancies, a form of community-based natural resource management (CBNRM). The article describes the activities of the Lion Rangers program, a CBNRM organization, emphasizing how the use of remote sensing techniques, including the Spatial Analysis and Report Tools (SMART) software and mobile-app, GPS/satellite collars, and trail cameras, contribute to lion monitoring and limiting human-lion conflict (HLC). Remote sensing data are being integrated with historical and sociological research, with applicable lessons for lion conservation and conservation of other problem-causing species.